Resveratrol induces dephosphorylation of Tau by interfering with the MID1-PP2A complex. Issue 1 (December 2017) - Schweiger, Susann; Matthes, Frank; Posey, Karen; Kickstein, Eva; Weber, Stephanie; Hettich, Moritz; Pfurtscheller, Sandra; Ehninger, Dan; Schneider, Rainer; Krauß, Sybille
Abstract The formation of paired helical filaments (PHF), which are composed of hyperphosphorylated Tau protein dissociating from microtubules, is one of the pathological hallmarks of Alzheimer's disease (AD) and other tauopathies. The most important phosphatase that is capable of dephosphorylating Tau at AD specific phospho-sites is protein phosphatase 2 A (PP2A). Here we show that resveratrol, a polyphenol, significantly induces PP2A activity and reduces Tau phosphorylation at PP2A-dependent epitopes. The increase in PP2A activity is caused by decreased expression of the MID1 ubiquitin ligase that mediates ubiquitin-specific modification and degradation of the catalytic subunit of PP2A when bound to microtubules. Interestingly, we further show that MID1 expression is elevated in AD tissue. Our data suggest a key role of MID1 in the pathology of AD and related tauopathies. Together with previous studies showing that resveratrol reduces β-amyloid toxicity they also give evidence of a promising role for resveratrol in the prophylaxis and therapy of AD.